A case of mottled hypopigmentation after low-fluence 1, 064-nm Q-switched neodymium-doped yttrium aluminum garnet laser therapy. (October 2013) - Ryu, Hwa Jung; Kim, Jiehoon
Abstract: Melasma is a very difficult pigmented disease to treat with high recurrence rate. Using low-fluence 1, 064-nm Q-switched neodymium-doped yttrium aluminum garnet (QSNY) lasers repeatedly for the treatment of melasma is now a common practice in East Asia. However, one of the significant side effects is mottled hypopigmentation that appears as scattered white macules in the middle of melasma lesion. The pathophysiology of these hypopigmentation is yet unknown. The biopsy of the hypopigmented lesion showed decreased melanosome with intact melanocytes, and topical tretinoin may be the effective solution for these types of condition.